1999
DOI: 10.1177/002076409904500403
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Subjective Quality of Life in Schizophrenic Patients Living in the Community. a Nordic Multicentre Study

Abstract: As part of a Nordic multi-centre study investigating the life and care situation of community samples of schizophrenic patients the aim of the present part of the study was to examine the relationship between global subjective quality of life and objective life conditions, clinical characteristics including psychopathology and number of needs for care, subjective factors such as satisfaction with different life domains, social network, and self-esteem. A sample of 418 persons with schizophrenia from 10 sites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
1
16

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 22 publications
8
58
1
16
Order By: Relevance
“…Adverse effects of treatment can have negative impacts on QOL of patients with medical illnesses [Yen et al, 2004]. Social support can reduce the impact of chronic stress on psychological well-being [Doeglas et al, 2004] and has been found to be associated with QOL in patients with severe mental [Hansson et al, 1999;KoivumaaHonkanen et al, 1996;Yanos et al, 2001] and chronic medical illnesses [Jaracz and Kozubski, 2003;Yen et al, 2004]. However, until now, little was known about the impacts of adverse QOL effects of pharmacotherapy for panic disorder, and only one study examined the relationship between QOL and perceived social support among patients with panic disorder [Katerndahl and Realini, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects of treatment can have negative impacts on QOL of patients with medical illnesses [Yen et al, 2004]. Social support can reduce the impact of chronic stress on psychological well-being [Doeglas et al, 2004] and has been found to be associated with QOL in patients with severe mental [Hansson et al, 1999;KoivumaaHonkanen et al, 1996;Yanos et al, 2001] and chronic medical illnesses [Jaracz and Kozubski, 2003;Yen et al, 2004]. However, until now, little was known about the impacts of adverse QOL effects of pharmacotherapy for panic disorder, and only one study examined the relationship between QOL and perceived social support among patients with panic disorder [Katerndahl and Realini, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…To date findings have been inconsistent. Some studies have found significant associations between subjective quality of life and clinician-rated psychopathology [11, 12, 13, 14]; on the other hand, a number of studies have reported only weak correlation between satisfaction with life and clinically assessed symptom severity [15, 16, 17], while others have failed to demonstrate any significant association between subjective quality of life and clinically evaluated levels of psychopathology [18, 19, 20]. These latter findings are consistent with the results of a recent study conducted by our group, which confirmed the lack of association, both cross-sectionally and longitudinally, between clinician-rated psychopathology and subjective quality of life [21].…”
Section: Introductionmentioning
confidence: 99%
“…The original 8 studies from which the full sample was drawn consisted of: (1) a Nordic multisite study [7], which investigated predictors of subjective well-being in community patients with schizophrenia in the 5 Nordic countries; (2) an explanatory-model study [8] comparing patients’ explanatory models for schizophrenia across 4 ethnic groups in a London community sample; (3) the DIALOG trial [9], which tested the effectiveness of a structured patient-clinician communication intervention in community samples across 6 European countries; (4) the EDEN trial [10], which compared day hospital versus inpatient treatment in 5 European countries; (5) InvolvE [11], which followed patients who had been involuntarily admitted to 22 UK hospitals; (6) EPOS [12], which tested the advanced DIALOG+ intervention involving a patient-centred solution-focused approach in a London community sample; (7) REFOCUS [13], a 2-site cluster randomised controlled trial testing the effectiveness of a staff-based intervention on recovery for patients with psychosis in England; and (8) NESS [14], which was a randomized controlled trial to examine the effectiveness of body psychotherapy for schizophrenia in several UK sites.…”
Section: Methodsmentioning
confidence: 99%